PENGARUH PENERAPAN TEAMS GAMES TOURNAMENT DALAM PEMBELAJARAN TEMATIK TERHADAP HASIL BELAJAR SISWA SEKOLAH DASAR - Espi, Aurelia; Kresnadi, Hery; Salimi, Asmayani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
Abstract This research aims to analyze the influence of implementanting Teams Games Tournament in thematic learning on student learning outcomes of fourth grade elementary school students 56 pontianak barat. Experimental method is in the form of pre experimental design research with one grup pretest-postest design. Population in this research consists of 39 students. Sampling teqnique used is purposive sampling. Data collection techniques used were measurement techniques, with data collection tools in the form of multiple choice. Based on statistical calculation obtained an average pre-test value of 61,67 and an average post-test value of 81.76. T test results obtained that tcount= 51,55 dan ttable ? = 0,01 (with dk= 39-1= 38) =39,80 it means tcount= 51,55 > ttable =39,80. Then alternative hypothesis (H1) is accepted. Based on the N-Gain analyze obtained value of 0,50 wich is categorizes as medium criteria. It can be concludes that there is an influence of implementanting teams games tournament in thematic learning on student learning outcomes of fourth grade elementary school students 56 pontianak barat Keywords: Influence, Teams Games Tournament, Student Learning Outcomes